INVESTIGATIONS ON THE STORAGE EFFICIENCY OF CO2 IN CARBONATE AQUIFERS - Sugihardjo Sugihardjo (Testing Center for Oil and Gas LEMIGAS, 2004)
The production of associated and nonassociated gas increases due to additional new oil and gas fields. Consequently, there will be an increase of CO2 released from associated gas, and especially, from nonassociated gas. Actually, CO2 may still be utilized in an attempt of increasing oil recovery through the methods of EOR (Enhanced Oil Recovery) or IOR (Improved Oil Recovery). In general, on the one hand, the CO2 availability in the atmosphere is still be needed for the photosynthesis process. But, on the other hand, this gas can stimulate the greenhouse effect that influences the global warming and weather changes. Prior being utilized, CO2 can be stored first in the depleted oil reservoirs or in the aquifers. The feasibility of these reservoirs or aquifers as a CO2 storage can be determined through the mechanisms of CO2 /water injection, or CO2 solubility in the water. For the purpose of several experiments, specific characters of the cores and formation water were decided taken from a representative carbonate reef formation in West Java region to substitute the samples from Natuna Field. The experiments were then continued on studying the CO2 solubility in the formation water not only at constant volume but also with varied volume, and also the CO2 storage efficiency in the carbonate rocks saturated with water.